(untitled) (Journal of Geography and Environmental Management, 2019)
This article addresses to the problems of formation of ecological tourism in the region. Assessment the ecological status of the territory and natural resources, the effect of physical and geographical condition for the development of ecotourism as well as the problem of arrangement ecotourist routes in the region are given here.